Diversity and compositional differences of the airborne microbiome in a biophilic indoor environment - Akinobu Toyoda; Yusuke Shibata; Yuzy Matsuo; Kumi Terada; Hiroki Sugimoto; Koichi Higashi; Hiroshi Mori; Akinori Ikeuchi; Masakazu Ito; Ken Kurokawa; Satoshi Katahira (Scientific Reports, 2023)
Abstract Biophilic design based on indoor planting plays an important role in human physical and mental well-being. To investigate and assess the effects of indoor planting on air quality, we sequenced 16S rRNA gene amplicons to compare the airborne bacterial microbiomes of three planting rooms before and after installing natural materials (plants, soil, water, etc.) with distinct biophilic attributes. Incorporation of indoor plantings significantly increased the taxonomic diversity of the airborne microbiome in each room, and we observed different microbiome compositions in each room. The proportional contribution of each bacterial source to the airborne microbiome in the indoor planting rooms was estimated by SourceTracker2. This analysis revealed that the proportion of airborne microbial sources (e.g., plants and soil) varied depending on the natural materials installed. Our results have important implications for indoor planting with biophilic design to control the indoor airborne microbiome.